2001
DOI: 10.1159/000050785
|View full text |Cite
|
Sign up to set email alerts
|

Homonymous Defect of Macular Vision in Ischemic Stroke

Abstract: It is generally believed that a homonymous defect of macular vision (HMV) is caused by a small lesion restricted to the occipital lobe tip and rarely results from ischemic stroke. The incidence of HMV was studied retrospectively in 54 patients with infarction of the posterior cerebral artery territory who underwent Goldmann’s visual field test. HMV was found in 6 patients (11%). In all of them, HMV was first dismissed due to a confrontation test of visual fields at the bedside and later detected by Goldmann’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Other types of visual field loss included inferior and superior quadrantanopia, constricted visual fields, scotomas, and altitudinal defects. Our findings were similar to those reported in the literature [1015]. Zhang et al [10] found that scotomas and macular sparing could not be localised to occipital lesions but could occur in other locations of the visual pathway: a statement with which we concur.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other types of visual field loss included inferior and superior quadrantanopia, constricted visual fields, scotomas, and altitudinal defects. Our findings were similar to those reported in the literature [1015]. Zhang et al [10] found that scotomas and macular sparing could not be localised to occipital lesions but could occur in other locations of the visual pathway: a statement with which we concur.…”
Section: Discussionsupporting
confidence: 93%
“…The most common type of visual field loss is that of homonymous hemianopia in which there is loss of the same half of the visual field in both eyes and which occurs in approximately two-thirds of those with visual field loss [79]. Other types of visual field loss may include inferior and superior quadrantanopia, constricted visual fields, scotomas, and altitudinal defects [1015]. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Homonymous hemianopia often remains undiagnosed in the pediatric population because children tend not to complain of a visual field defect and usually are not referred for formal visual field testing. However, recognition of visual field defects in children with cerebral insults is important because homonymous hemianopia may interfere with learning, reading, rehabilitation therapies, and driving abilities.…”
mentioning
confidence: 99%
“…[21][22][23] Other types of visual field losses may include inferior and superior quadrantanopia, constricted visual fields, scotomas, and altitudinal defects. [24][25][26][27][28] Pambakian and Kennard reported visual field losses due to an occipital lobe lesion in 40%, a parietal lobe lesion in 30%, a temporal lobe lesion in 25%, and 5% with damage to the optic tract and lateral geniculate nucleus. 29 Zhang et al reported the area of stroke as the occipital lobe in 54%, optic radiations in 33%, the tract in 6%, lateral geniculate nucleus in 1%, and 5% with multiple pathway segment involvement.…”
Section: Discussionmentioning
confidence: 99%